An International Approach to Environmental Business Rights and Energy Sustainability Throught the Lenses of the Competition Law - Gómez-Rodríguez, Juan Manuel (2023)
This article examines the principles of environmental law and its relationship with business rights, as well as the principles of regulation of energy law, particularly those related to economic efficiency and environmental sustainability. We consider both principles must be harmonized through competition law considering energy sustainability. Likewise, the collaboration among governments, companies, environmentalists, and consumer organizations is necessary to design a regulation articulating a new understanding of rights toward sustainable energy management.